Generation and flow cytometric quality control of clinical‐scale TCRαβ/CD19‐depleted grafts. Issue 2 (14th December 2015) - Bremm, Melanie; Cappel, Claudia; Erben, Stephanie; Jarisch, Andrea; Schumm, Michael; Arendt, Andreas; Bonig, Halvard; Klingebiel, Thomas; Koehl, Ulrike; Bader, Peter; Huenecke, Sabine
Abstract : Background: The depletion of TCRαβ + T cells and CD19 + B cells is a graft purification method for haploidentical stem cell transplantation (HSCT) retaining stem cells, NK cells and TCRγδ + T cells. To avoid treatment‐related occurrence of severe GvHD a precise quantification of residual TCRαβ + T cells in the graft is of essential importance. Methods: Nine stem cell grafts were purified immunomagnetically on a CliniMACS device and flow cytometric quality control (QC) was performed before and after TCRαβ/CD19‐depletion. Results: As a challenge a new 10‐color QC‐panel was established, which enables accurate quantification of the graft composition. The binding sites of residual TCRαβ + T and CD19 + B cells were at least partly occupied by depletion antibodies impeding flow cytometric analysis. Based on respective controls and an assumed variation coefficient of 18%, the detection limit of residual TCRαβ T cells was 1 cell/µl. and 0.002% of CD45 + cells. Log‐depletion of TCRαβ and CD19 cells was −3.9 and −3.3, respectively. The recovery was 82.1%, 67.1% and 72.7% for stem cells, NK cells and for TCRγδ + T cells. Conclusions: In clinical use this method may help to improve transplantation outcome, due to the correct application of the desired stem cell and the limited T cell dose. The panel is designed for the QC following TCRαβ/CD19‐depletion but is adaptable to other depletion strategies as well. © 2015 International Clinical Cytometry Society